PENGARUH KOMPETENSI SUPERVISI KEPALA SEKOLAH TERHADAP PENINGKATAN MUTU PEMBELAJARAN - Kartini, Kartini (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The principal's supervisory competence provides a great influence on increasing teacher professionalism. This study aims to describe: (1) the competency of principals in developing academic supervision programs to improve teacher professionalism, (2) competency of principals in implementing or implementing academic supervision programs to improve teacher professionalism, and (3) competency of principals in giving action continued academic supervision results to improve teacher professionalism. This study uses a descriptive method with a qualitative approach. Data collection techniques are used through observation, interviews, and documentation studies. The research subjects were principals, vice principals, teachers, and school supervisors at Suak Tapeh 3 Public High School. The results of the study showed that: (1) Head of SMP 3 Suak Tapeh had shown good supervision competence, especially in preparing academic supervision programs for teachers. (2) Head of SMP 3 Suak Tapeh had demonstrated good supervision competence, especially in implementing academic supervision programs. . (3) Supervision competence of the head of SMPN 3 Suak tapeh especially in following up the results of supervision is still lacking.